A call to expand disciplinary boundaries so that social scientific imagination and practice are central to quests for 'responsible' digital agri‐food innovation. Issue 2 (29th April 2022) - Fielke, Simon; Bronson, Kelly; Carolan, Michael; Eastwood, Callum; Higgins, Vaughan; Jakku, Emma; Klerkx, Laurens; Nettle, Ruth; Regan, Áine; Rose, David C.; Townsend, Leanne C.; Wolf, Steven A.
Abstract: This editorial introduces a special issue (SI) concerning quests for responsible digital agri‐food innovation. We present our interpretations of the concepts of responsible innovation and digital agri‐food innovation and show why they can and have been productively interrelated with social science theories and methods. First, each of the articles in this SI is briefly introduced and synthesised around three themes: (1) the need for a critique of digital 'solutionism' in current interdisciplinary research, development and innovation settings; (2) that social science contributes value via the ideas it brings to life to challenge dominant power dynamics and (3) that social scientific imagination and practice is a valuable long‐term investment to both mitigate risk but also embrace socioenvironmental opportunities as we face ongoing sustainability crises into the future. Second, we identify future research considerations arising within the field, sitting at the intersection of social science and agricultural sociotechnical transitions. Our insights relate to challenges and opportunities to 'do' social science within the context of contemporary and nascent transitions such as increasing digitalisation. Researchers trained in social science theory and practice can make distinctive contributions to agri‐food innovation processes by making social stakes visible and by advancing inclusive processes of research policy and technology design.